Preface [Hot topic: Protein Misfolding in the Amyloidoses and other Disorders (Guest Editor: David R. Howlett)] - Howlett, David R. (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2003)
The term amyloid was initially generally used to describe macroscopic abnormalities which became evident only at autopsy of patients succumbing to a variety of disease states. The advent of histopathological, biochemical and molecular biological techniques, however, has resulted in great advancement in our understanding of amyloid structure. Deposits of amyloid proteins are now recognised as being of diverse origin and chemical make-up, all types of which exhibit a fibrillar structure when viewed by electron microscopy. They are further characterised by their cross-β structure, which confers specific tinctorial properties (Congo red and thioflavin S binding) and resistance to proteolytic degradation. These properties are conferred upon the different amyloids by interactions in the main backbone chain of the molecules and specific sequence effects are usually not of great significance in structure determinance. In the Neurosciences, the term “amyloid” invariably leads many to believe that it is the beta-amyloid or ABeta of Alzheimer's disease which is being discussed. In fact, a crude literature trawl shows that in the 1970-80 decade only 2% of amyloid publications described Alzheimer's disease. The following decade saw this proportion increase to 17% and then to 48% in the last decade of the 20th century; since the Millenium it stands at 56%. It is perhaps fitting, therefore, that this volume of CMC-IEMA begins with the ABeta peptide. Since its biochemical elucidation in 1984, the amyloid protein of AD plaque has been termed beta-amyloid, beta- A4, amyloid-β-peptide, Aβ and ABeta. It should be noted that much of the reported in vitro work with Aβ peptide employs something of a misnomer as the peptide monomer is neither an amyloid, in the strictest sense of the word, nor does it always exhibit beta-pleated sheet structure. Poetic licence has been permitted, however, and no attempt made to standardise (or correct) the nomenclature in the present reviews. Although the biochemical identity of the Ab peptide has been known for two decades, the precise form of the peptide and the means by which it affects its purported neurodegeneration is far from clear. Thus, the volume starts with Walsh and colleagues who explore “The Many Faces of Ab”, reviewing the literature investigating the role of oligomers, protofibrils, ADDL's and fibrils in the development of AD pathology. Even without knowledge of the precise identity of the toxic form of Aβ, most Alzheimer's literature supports The Amyloid Hypothesis, originally proposed in the early 90's. Opposing this, however, we are able to consider the evidence presented by Lee and colleagues who assert that Aβ is the innocent victim of mistaken identity and that the production of the protein is actually the body's attempt to deal with stress and injury. This is a theme that I have also attempted to explore in the final review dealing with a number of amyloidoses and protein conformational disease, how protein misfolding occurs and how the body attempts to deal with what is sees essentially as a foreign body. Overwhelming evidence shows that misfolded proteins are pathological features of their respective disease states - but are they the villains or innocent by-standers? Evidence for a direct effect of aggregated peptides on cell death is presented by Tabner et al. who propose that the production of reactive oxygen species is a fundamental pathological process in many neurodegenerative disorders. Linked to this is the role that metal ions, principally copper and zinc, play in oxidative damage. Curtain and colleagues discuss metal ions, with particular attention being paid to the emerging data with the chelating agent clioquinol. Aβ deposition is also the characteristic feature of cerebrovascular amyloid angiopathy. The importance of these vascular deposits in the pathogenesis of Alzheimer's disease and dementia in general is reviewed by Kalaria et al. Aside from Aβ, this edition of CMC-IMEA deals with a detailed consideration of a number of other misfolded proteins. Rubinsztein discusses the polyQ huntingtin protein in Huntington's disease and explores how cells deal with aggregated and misfolded proteins to protect against excitotoxicity. Neurofibrillary tangles comprising aggregates of hyperphosphorylated tau are a major pathological feature of Alzheimer's and other neurodegenerative diseases such as progressive supranuclear palsy and Pick's disease. Goedert discusses the function of tau and the role of tau aggregation in these disorders. Moving away from the CNS, Brito et al. describe the folding mechanisms underlying the amyloid formation by transthyretin in peripheral diseases such as senile systemic amyloidosis. Therapeutic agents capable of preventing the aggregation or misfolding of proteins associated with the diseases discussed above have long been a scourge of Medicinal Chemists. Difficulties in determining xray structure (particularly with Aβ) and the very nature of protein-protein interactions have hindered the development of potential therapeutics. Advances are being made, however, and Gervais et al. discuss the role of proteoglycans in promoting amyloid formation and how this knowledge is leading towards the discovery of compounds capable of interfering with proteoglycan-amyloid binding. Proteins are dynamic structures that display continuous conformational change throughout their lives from initial translation to eventual degradation. Understanding these changes and the nature of protein folding mechanisms should lead to the discovery of drugs capable of protecting cells from injury. The reviews presented in this edition of CMC-IMEA hopefully provide an insight into both the progress being made but also of the difficulties that still remain.